An Analysis of Code Mixing Used by University Students in Social Media - Azhar Novriansyah (Universitas Syiah Kuala, 2023)
This descriptive qualitative research is aimed to discover types of code mixing used by English students and to specify the reasons of why students using code-mixing in WhatsApp group chat. The data of this study were obtained from all of the English students that use code-mixing in two of the WhatsApp group chats, that are Aneuk Agam ESA Unsyiah, and English USK 17. The data of this research were collected by using WhatsApp application and interview. The data taken from two of the WhatsApp group chats from September 2022 to the end of 2022. The whole interaction between group chat population were transcribed and analyzed. The results showed that students used three types of code-mixing, with dominant type of insertion, followed by alternation, and congruent lexicalization. Insertion type of code-mixing itself found divided into three level, with dominant type is noun level of code-mixing, followed by adjective level of code-mixing, and verb level of code-mixing. Another result found code-mixing was most often used because of habitual patterns. Furthermore, Students in the related Whatsapp group chats reported that there were two reasons why they code-mix beside of habitual patterns: it is because of participant roles and relationship as well as of situational factors.